Modelagem numérica no ensino de fenômenos dinâmicos: um exemplo na farmacologia - Segura, Francisco Novales (Universidade Federal de São Carlos, 2019)
The teaching of phenomena in the sciences now passes through a paradigm shift. Seeking an increase in interest in scientific careers, it is desired to deepen the understanding of those through mathematics, so that it is not restricted to exposition of concepts and presentation of formulas to the students. To this end, appropriate instruments must be used, the choice of which should occur based on the evidence gathered from the research already carried out. In this tuning fork, mathematical modeling and the use of technology stand out. From the crossing of these, numerical methods arise in the resolution of mathematical models of phenomena, especially the dynamic ones, whose leadership in applications and adaptation to the scientific method justify our gaze. Therefore, we present here an activity designed to explore the scientific theme pharmacology in high school and higher education, especially in careers in the biological sciences.
Numerical modeling in the teaching of dynamic phenomena: an example in pharmacology
Keywords: Matemática; Métodos numéricos; Modelagem quantitativa; Biologia; Farmacologia; Educação; Ensino de ciências; Mathematics; Numerical methods; Quantitative modelling; Biology; Farmacology; Education; Sciences teaching; CIENCIAS BIOLOGICAS::FARMACOLOGIA; CIENCIAS DA SAUDE::FARMACIA; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA GERAL::FARMACOCINETICA; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA; OUTROS::CIENCIAS